The pilot-scale preparation of the SA-hGM-CSF bi-functional fusion protein. Issue 1 (1st January 2019) - Li, Xiaoqing; Zhou, Shirong; Wang, Yao; Lian, Hui; Zuo, Anxin; Zhou, Kaihua; Tong, Ling; Zhou, Zhujun; Gao, Jimin
ABSTRACT: The granulocyte-macrophage colony-stimulating factor (GM-CSF) can be used to induce a powerful immune response. Based on the specific binding of biotin and streptavidin, SA-hGM-CSF was anchored on the surface of biotinylated tumor cells, which could enhance the anti-tumor effect of tumor cell vaccines in our previous reports, suggesting it would have potential clinical value. Preparation of the biologically active proteins in large-scale production is the basis of clinical application, however, only a small amount of biologically active protein was obtained according to previous studies. In this study, we researched the effects of various factors on the purification and simultaneous renaturation of SA-hGM-CSF fusion protein by single factor experiment and orthogonal experiment. Here, we developed a viable pilot-scale trial in the fermentation, purification, refolding and freeze-drying of SA-hGM-CSF proteins in order to efficiently obtain more biologically active proteins with high purity, which will lay the foundation for industrial production.